Comprehensive case management of malaria: Operational research informing policy - M M Pradhan; Anupkuamar R Anvikar; P Grewal Daumerie; S Pradhan; A Dutta; N K Shah; P L Joshi; J Banerji; S Duparc; K Mendis; S Murugasampillay; N Valecha (Journal of Vector Borne Diseases, 2019)
In 2013, the Odisha state Vector Borne Disease Control Programme led a five year operational research project, under programmatic conditions, in close collaboration with several partners. This Comprehensive Case Management Project covered a population of 900,000 across paired control and intervention blocks in four districts, each with different transmission intensities. Key gaps in access to malaria services were identified through household surveys and a detailed situation analysis. The interventions included ensuring adequate stocks of rapid diagnostic tests and antimalarial drugs at the village level, the capacity building of health workers and ASHAs, setting up microscopy centres at the primary health care level, and conducting mass screening and treatment in poorly accessible areas. The programme strengthened the routine health system, and improved malaria surveillance as well as the access to and quality of care. Initially, the programme led to increased case reporting due to improved detection, followed by a decline in malaria incidence. Lessons from the project were then scaled up statewide in the form of a new initiative—Durgama Anchalare Malaria Nirakaran (DAMaN).